Estado actual de los docentes de Imagenología para la gestión del conocimiento en red. Universidad de Ciencias Médicas Holguín, Cuba. - Cabrales Fuentes, José; Burguet Lago, Ivonne; Gómez Ríos, Sadia Lumis (Revista Cubana de Informática Médica)
Introduction: In our environment, the current health systems are not well designed to gain the existing knowledge, evaluate, share and apply it from the network, as well as to produce it in our area if the available knowledge is insufficient or questionable. Objective: To know the current status of Imaging teachers for online knowledge management. Method: A descriptive exploratory study was performed on the staff of 46 teachers from the Imaging Department of the of the University of Medical Sciences of Holguín between November 2022 and February 2023 in order to know their current status for online knowledge management. A reliable tool of 10 closed questions was designed and applied. Results: Deficiencies, which constitute essential particularities for the adequate development of online knowledge management, were revealed in Imaging teachers. Conclusions: It is evident that the Imaging teachers do not get the most out of the potential of the networks for knowledge management and the treatment of the Imaging contents, so it is necessary to develop a pedagogical strategy that allows breaking with the established traditional dynamics, since they have proven not to be always effective in the process of improving the performance of teachers in this specialty.